James Riley Weaver's Civil War : The Diary of a Union Cavalry Officer and Prisoner of War, 1863-1865 - Weaver, James Riley, 1839-1920 (Civil War soldiers and strategies., 2019)
666 days of diary entries documenting the life of a Union officer held in Confederate prisons. Captured on October 11, 1863, James Riley Weaver, a Union cavalry officer, spent nearly seventeen months in Confederate prisons. Remarkably, Weaver kept a diary that documents 666 consecutive days of his experience, including not only his life in a series of prisons throughout the South, but his precaptivity cavalry duties, and his eventual return to civilian life. It is an unparalleled eyewitness account of a crucial part of our history. Weaver's observations never veer into romanticized descriptions; instead, he describes the "little world" inside each prison and outdoor camp, describing men drawn from "every class of society, high and low, rich and poor, from every country and clime." In addition, Weaver records details about life in the Confederacy that he gleans from visitors, guards, new arrivals, recaptured escapees, Southern newspapers, and even glimpses through windows. As the editors demonstrate, Weaver's diary-keeping provided an outlet for expressing suppressed emotions, ruminating on a seemingly endless confinement that tested his patriotism, religious faith, and will to survive. In the process, he provides not only historically important information but also keen insights into the human condition under adversity.